Tumor versus stromal cells in culture--survival of the fittest? - Krishna M Talasila (Public Library of Science (PLoS), 2013)
Two of the signature genetic events that occur in human gliomas, EGFR amplification and IDH mutation, are poorly represented in experimental models in vitro. EGFR amplification, for example, occurs in 40 to 50% of GBM, and yet, EGFR amplification is rarely preserved in cell cultures derived from human tumors. To analyze the fate of EGFR amplified and IDH mutated cells in culture, we followed the development over time of cultures derived from human xenografts in nude rats enriched for tumor cells with EGFR amplification and of cultures derived from patient samples with IDH mutations, in serum monolayer and spheroid suspension culture, under serum and serum free conditions. We observed under serum monolayer conditions, that nestin positive or nestin and SMA double positive rat stromal cells outgrew EGFR amplified tumor cells, while serum spheroid cultures preserved tumor cells with EGFR amplification. Serum free suspension culture exhibited a more variable cell composition in that the resultant cell populations were either predominantly nestin/SOX2 co-expressing rat stromal cells or human tumor cells, or a mixture of both. The selection for nestin/SMA positive stromal cells under serum monolayer conditions was also consistently observed in human oligodendrogliomas and oligoastrocytomas with IDH mutations. Our results highlight for the first time that serum monolayer conditions can select for stromal cells instead of tumor cells in certain brain tumor subtypes. This result has an important impact on the establishment of new tumor cell cultures from brain tumors and raises the question of the proper conditions for the growth of the tumor cell populations of interest.